2024
DOI: 10.3390/vision8010006
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Assessment of Fine Motor Skills in Children: Comparison of a Kinematic Approach and a Standardized Test

Ewa Niechwiej-Szwedo,
Taylor A. Brin,
Benjamin Thompson
et al.

Abstract: Deficits in fine motor skills have been reported in some children with neurodevelopmental disorders such as amblyopia or strabismus. Therefore, monitoring the development of motor skills and any potential improvement due to therapy is an important clinical goal. The aim of this study was to test the feasibility of performing a kinematic assessment within an optometric setting using inexpensive, portable, off-the-shelf equipment. The study also assessed whether kinematic data could enhance the information provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…When analyzing differences between 6YC and 7YC groups, corresponding to two different school grades, results indicate that 7YC generally exhibited shorter task completion times (PBtime), Cycle and Placing durations, and lower variability of Cycle compared to 6YC, highlighting the expected improvements in fine motor skills with age and with school education. While direct comparison is not possible due to there being different tasks and age groups under consideration, Placing duration tended to decrease with age maturation as for the quantitative assessment of fine MABC-2 [11]. Differences were higher for the dominant hand, probably as a consequence of the intensive training that happens during the first year of primary school with the learning of writing skills.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When analyzing differences between 6YC and 7YC groups, corresponding to two different school grades, results indicate that 7YC generally exhibited shorter task completion times (PBtime), Cycle and Placing durations, and lower variability of Cycle compared to 6YC, highlighting the expected improvements in fine motor skills with age and with school education. While direct comparison is not possible due to there being different tasks and age groups under consideration, Placing duration tended to decrease with age maturation as for the quantitative assessment of fine MABC-2 [11]. Differences were higher for the dominant hand, probably as a consequence of the intensive training that happens during the first year of primary school with the learning of writing skills.…”
Section: Discussionmentioning
confidence: 98%
“…When aiming to analyze the process of how a movement is performed, motion capture systems are preferrable. Recently, Niechwiej-Szwedo et al, [11] confirmed the feasibility and the promising pathway of performing a quantitative kinematic assessment within an optometric setting using inexpensive, portable, off-the-shelf equipment (Leap motion capture system) for enhancing the information provided by a routine motor function screening test (bead-threading task, fine MABC-2, [6]). They proposed a quantitative method for estimating the duration of sub-phases of each bead-threading trial (reach to bead, grasp and pick up bead, reach to needle, and place the bead on a needle), based on the analysis of hand velocity trajectory.…”
Section: Introductionmentioning
confidence: 98%